Desain Media Bantu Berbasis Multimedia untuk Pengoperasian Mesin ID Card pada 75 Center Design Graphic Studio - Fitro Nur Hakim; M. Abdurrahman Bahyhaq Andica P (STEKOM PRESS, 2022)
The company 75 Center Design Graphic Studio is a provider of printing services and design services that serve the manufacture of various printing products. One of the problems that often arise when working on orders from customers is that there are many orders while there is only one expert, so there is not enough time to do it. Using technological advances, learning aids are made, which can later be used by employees to operate the ID Card machine. This learning aid media will display an autoplay program containing the process of making product from beginning to end. This learning aid media is made based on Multimedia.